1981
DOI: 10.1159/000112815
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of <sup>3</sup>H-Diazepam Binding Sites in Different Rat Brain Area

Abstract: The ontogenesis of the 3H-diazepam binding sites and their modulation by gamma-aminobutyric acid have been studied in different brain areas of rat at various ages, using frozen and two Triton X-100 treated crude synaptic membrane preparations. Benzodiazepine recognition sites are present at birth in all the brain regions investigated and reach adult levels about 3 weeks later. The changes of 3H-diazepam binding with age are due to an increase in the total number of binding sites. In vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The increase in [3H]-diazepam binding during development is due to a large number of binding sites rather than to a higher affinity for [3H]-diazepam. These results are in accordance with those reported by Braestrup and Nielsen [1978], Candy and Martin [1979], Mallorga et al [1980], and Aldinio, et al [1981] who have shown that benzodiazepine receptors are present in the rat brain at an early stage of development and reach a maximal concentration after about 4 weeks. The present study also establishes that methylxanthines such as caf feine and theophylline and purine compounds are able to displace the spe cific diazepam binding in cerebral membranes from adult rats as already demonstrated by Marangos et al [1979].…”
Section: Discussionsupporting
confidence: 93%
“…The increase in [3H]-diazepam binding during development is due to a large number of binding sites rather than to a higher affinity for [3H]-diazepam. These results are in accordance with those reported by Braestrup and Nielsen [1978], Candy and Martin [1979], Mallorga et al [1980], and Aldinio, et al [1981] who have shown that benzodiazepine receptors are present in the rat brain at an early stage of development and reach a maximal concentration after about 4 weeks. The present study also establishes that methylxanthines such as caf feine and theophylline and purine compounds are able to displace the spe cific diazepam binding in cerebral membranes from adult rats as already demonstrated by Marangos et al [1979].…”
Section: Discussionsupporting
confidence: 93%
“…It is further corroborated by the observation that the labeling pattern was virtually identical for FNZP and the specific BDZ antagonist Ro 15-1788 (Darragh et al, 1981;Hunkeler et al, 1981). Biochemical studies indicate that the affinity characteristics of BDZ-binding sites do not noticeably change during ontogeny (Braestrup and Nielsen, 1978;Mallorga et al, 1980;Aldinio et al, 1981). Whether there are changes in the relationship to the GABA receptor remains uncertain.…”
Section: Discussionmentioning
confidence: 87%
“…At birth, these receptors are present at a relatively high density and they reach adult levels about 3 wk later. During postnatal development, the increase in benzodiazepine binding has been demonstrated to be due to a larger number of specific sites, rather than to a higher receptor affinity (21)(22)(23). A sequential development of benzodiazepine receptors in relation to the time course of maturation of cerebral structures could be shown, with a proliferation peak that parallels rapid brain growth in the rat (between 5 and 15 d of age).…”
Section: Development Of Central Benzodiazepine Receptorsmentioning
confidence: 99%